2011
DOI: 10.1134/s1070428011120098
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of the hydrolysis of 2-(1-alkoxyvinyl)-substituted imidazolidines, 1,3-thiazolidines, and 1,3-oxazolidines

Abstract: 2-(1-Alkoxyvinyl)-1,3-thiazolidines reacted with H 2 O or D 2 O in the presence of 105 mol % of p-toluenesulfonic acid or trifluoroacetic acid (20°C, 1 h) to give 2-acetyl-1,3-thiazolidine in quantitative yield. 2-(1-Alkoxyvinyl)-3,5-diphenylimidazolidines underwent hydrolysis in the presence of 20 mol % of an acid (20°C, 24 h) at the vinyloxy group with high regioselectivity yielding 2-acetylimidazolidines. Hydrolysis of 2-(1-alkoxyvinyl)-3-phenyl-1,3-oxazolidines in the presence of 10 mol % of p-toluenesulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The authors found that the introduction of substituents into the oxazolidine ring enhanced the stability of the cyclic form (Scheme ) . Regioselective MWI‐promoted hydrolysis of 2‐(1′‐ethoxyvinyl)‐3‐phenyl‐1,3‐oxazolidine across the vinyloxy group allowed 2‐acetylsubstituted analogues 180 a to be synthesized in up to 70 % yield . Notably, these compounds could not be prepared from glyoxals …”
Section: Oxazolidines (Tetrahydro‐oxazoles) and 2‐oxazolines (45‐dmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the introduction of substituents into the oxazolidine ring enhanced the stability of the cyclic form (Scheme ) . Regioselective MWI‐promoted hydrolysis of 2‐(1′‐ethoxyvinyl)‐3‐phenyl‐1,3‐oxazolidine across the vinyloxy group allowed 2‐acetylsubstituted analogues 180 a to be synthesized in up to 70 % yield . Notably, these compounds could not be prepared from glyoxals …”
Section: Oxazolidines (Tetrahydro‐oxazoles) and 2‐oxazolines (45‐dmentioning
confidence: 99%
“…The interaction of thiazolidine 216 a with excess (105–107 %) p TsOH or CF 3 COOH (TFA) in water or D 2 O proceeded through easy regiospecific hydrolysis of the alkoxyvinyl group to furnish 2‐acetyl‐1,3‐thiazolidine 218 , which was readily isolated as the tosilate, in up to 100 % yield (by 1 H NMR spectroscopy) . This reaction opened an access to cyclic thioaminals of methylglyoxal, which were previously obtained as a mixture of three products from the scarcely available and easily polymerizable methylglyoxal …”
Section: Thiazolidines (Tetrahydrothiazoles)mentioning
confidence: 99%